Comunicação pública e sustentabilidade: estudo da comunicação mediada do projeto Manuelzão - Silva, Ana Carolina Feliciano da [UNESP] (2017)
This publication presents the results of a research that seeks to identify and characterize the potential contribution of public communication of Manuelzão magazine editions (2015-2016), maintained and created by Projeto Manuelzão according to the categorical content analysis methodology. Projeto Manuelzão, created in 1997, is structured in groups that aim to contribute to the elaboration and execution of goals related to water management, environmental education and participation in the formulation and evaluation of public policies related to watershed. Manuelzão magazine is one of the arms of the Project and seeks to develop critical thinking on political and socio-environmental issues related to water resources and the environment. According to the methodology, the 50 articles presented in the respective editions were analyzed and it was obtained: a) characterization of the depth and comprehensiveness of information available in the 2015-2016 editions of Manuelzão magazine; b) the identification of the community context, the biography of militants, the management of public spaces, sustainability issues, institutional achievements, public actions and the involved sectors and the development experiences of Projeto Manuelzão, in relation to seven categories of analysis: political, social and economic scenario; legal information and technological development; information about memory and project history; goals and objectives; planning and metrics; dialogues with social actors and plurality of voices (excluding public sector) and dialogues with the public sector. Articles evaluated obtained 58.86% of Information Quality Index, it is slightly more than half of information about the categories considered essential for what is understood as public quality communication. In view of the results obtained, it was suggested a guide for production and publicizing a deepth and comprehensive information...